APPLICATION OF PROJECT BASED LEARNING TO IMPROVE STUDENTS’ CREATIVITY IN THEME 7 “THE BEAUTY OF DIVERSITY IN MY COUNTRY” TO FOURTH GRADE STUDENTS OF SDN 1 KUTOSARI IN ACADEMIC YEAR OF 2021/2022 - Rida Nuriyah Phasa; Ngatman Ngatman; Rokhmaniyah Rokhmaniyah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2022)
The study aimed to improve students’ creativity in social science learning about Theme 7 “The Beauty of Diversity in My Country through Project Based Learning. The classroom action research was carried out in two cycles. The subjects were teachers and fourth grade students of SDN 1 Kutosari. The data were qualitative and quantitative data. Data collection techniques used observation, interviews, documentation and tests. The data validity used triangulation of sources and triangulation of techniques. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results indicated that the application of Project-Based Learning improved students’ creativity about “The Beauty of Diversity in My Country. The percentages of students’ creativity were 74.99% in the first cycle and 85.98% in the second cycle. It concludes that the application of Project Based Learning improves students’ creativity in social science learning about Theme 7 “The Beauty of Diversity in My Country to fourth grade students at SDN 1 Kutosari in academic year of 2021/2022.